2013
DOI: 10.1590/s1806-83242013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Radiodensitometric and DXA analyses for the measurement of bone mineral density after systemic alendronate therapy

Abstract: Precise techniques for the measurement of maxillary bone mineral density (BMD) are useful for the early diagnosis of systemic diseases. The aim of this study was to compare in vivo the efficacy of dualenergy x-ray absorptiometry (DXA) and radiographic densitometry for the measurement of BMD after systemic administration of sodium alendronate. Wistar rats were randomly allocated to a control group (n = 5), which received distilled water, and a sodium alendronate group (n = 8), which received two doses of chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
6
0
6
Order By: Relevance
“…Por otro lado, Lucisano et al (2013) analizaron la DMO en ratas, después de la administración sistémica de AL, utilizando dosis de 1 mg/kg por semana. En su trabajo demostraron una DMO significativamente mayor que el grupo control recién después de 8 semanas de tratamiento (60 días).…”
Section: Discussionunclassified
“…Por otro lado, Lucisano et al (2013) analizaron la DMO en ratas, después de la administración sistémica de AL, utilizando dosis de 1 mg/kg por semana. En su trabajo demostraron una DMO significativamente mayor que el grupo control recién después de 8 semanas de tratamiento (60 días).…”
Section: Discussionunclassified
“…We also investigated the bone mineral density (BMD) that is widely used to evaluate alterations in the balance between osteoblastic bone formation and osteoclastic bone resorption ( 25 ). The measurement of BMD through radiographic densitometry has been performed in a number of studies, and its efficacy has been confirmed ( 25 - 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the bone mineral density (BMD) that is widely used to evaluate alterations in the balance between osteoblastic bone formation and osteoclastic bone resorption ( 25 ). The measurement of BMD through radiographic densitometry has been performed in a number of studies, and its efficacy has been confirmed ( 25 - 27 ). Radiographic densitometry analysis is an important tool for the research evaluation because it is a rapid and low-cost method, and can produce results which are similar to those of dual-energy x-ray absorptiometry ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The data were recorded and analysed by the Lunar PIXImus software, version 2.2 (Lunar PIXImus Corp. Headquarters), as described previously (Lucisano et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…One femur from each animal of all groups was surgically removed and analysed by Lunar PIXImus dual-energy X-ray absorptiometry densitometry (Lunar PIXImus Corp. Headquarters, Madison, WI, USA) for recording the BMD of the distal metaphysis, in g cm À2 . The data were recorded and analysed by the Lunar PIXImus software, version 2.2 (Lunar PIXImus Corp. Headquarters), as described previously (Lucisano et al 2013).…”
Section: Ovx Effectiveness Confirmationmentioning
confidence: 99%